PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN UMUR PERUSAHAAN PADA PENGUNGKAPAN INFORMASI LINGKUNGAN - Ciriyani, Ni Ketut; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Amount of environmental damage problem that occurred in Indonesia, making a lot of environmental aspect become a hot discussion among the public. To show the company’s attetion and awareness about environmental then the company makes environmental activities disclosure that contained in yearly repots that they publish. This research purposed to find out the effect of the company’s size, profitability, and the company’s age on the environmental disclosure. The population in this research are all companies that was registered on the Indonesia Stock Exchange in 2012-2014 and was registered in the PROPER. Sampling method used was purposive sampling. Amount of sampling used was 29 companies. Data collection method used non participant observation and documentation. Analytical techniques used was multiple linier regression. Based on analystical result was found that the company’s size and the company’s age has positive effect on the environmental disclosure. While profitability has no effect on the environmental disclosure.
Keywords: environmental disclosure, company’s size, profitability, company’s age, proper